(untitled) (Indian Journal of Chemistry (IJC), 2025)
A new series of 2-((E)-2-(Thiophen-2-yl)vinyl)-4H-chromen-4-ones were synthesized and characterized by mass, IR, PMR and CMR spectroscopy. The characterization data supports the formation of synthesized compounds. All the synthesized compounds were investigated for antibacterial activity against Pseudomonas flurescence (NCIM 2059), Escherichia coli (NCIM 2576) as Gram negative and Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162) as Gram positive bacteria at different concentrations and they show moderate to good antibacterial activity.